Scientometric approaches to the analysis of research results - R. G. Oganov; S. A. Trushchelev (Кардиоваскулярная терапия и профилактика, 2012)
The paper discusses the role of scientific medical information and its impact indicators (researcher’s publishing activity, citation index, impact factor, Hirsch index, etc.). The sources of these indicators are specified.